Pensamento científico e narrativa transmídia: uma plataforma digital para a aprendizagem científica e criativa - Ebert, Vagner (2022)
The development of scientific thinking is an emerging theme in contemporary teaching and learning processes, being important for the formation of individuals capable of building knowledge in an active, autonomous and critical way. In this sense, the present study seeks to answer the following research problem: What are the characteristics of a digital platform that supports pedagogical proposals based on scientific thinking? Therefore, the objective is to analyze evidence of the development of scientific thinking from the use of a digital platform. In order to answer the proposed question and achieve the objectives, the research is developed in the form of a qualitative, applied and exploratory study, and uses the Design Science Research method (DRESCH, 2020) to develop an artifact, namely the digital platform YepYou!. Based on the use of this artifact by educators, the production of data for empirical research is carried out. The theoretical framework is based on the understanding of what is meant by scientific thinking based on Bachelard (1996), expanding the study to issues related to creative learning (RESNICK, 2020), active methodologies (MORAN, 2018), the approach STEAM and the maker movement, in addition to proposing the investigation of transmedia storytelling concepts based on Jenkins (2009a), storytelling (PALACIOS, TERENZZO, 2016) and the Hero's Journey (CAMPBELL, 2007; VOGLER, 2015). The application of the research was based on a pilot test and the subsequent final application carried out by educators with students in the 6th year of basic education. The study revealed that the characteristics of a platform aimed at promoting scientific thinking consist in the development of curiosity, dialogue and innovation and that such a platform contributed to the development of autonomy in student learning, as well as to the mediation of the educator, an aspect which, in this way, proved to be fundamental for the construction of knowledge based on scientific thinking. The results obtained also point out the importance of the narrative, through the characters and the plot, in the student's engagement and in the awakening of their curiosity, but they proved to be limited in terms of transmedia elements. It is concluded that the platform contributes to the development of scientific thinking, facilitates pedagogical mediation and stimulates curiosity, engagement, dialogue and innovation in teaching and learning processes.